Correlation Between Fibrinolytic Activity and Endocrine Regulation During Adaptation to Physical Load - Natalya A. Malyshkina; Nadezhda A. Vorobyeva (Журнал медико-биологических исследований)
Corticosteroids are one of the key hormones contributing to the development of general adaptation syndrome. The initial phase of stress changes in the haemostatic system during adaptation to physical activity is hypercoagulation, which is dangerous for the body due to increased thrombosis. If the exercise is adequate for the body’s adaptive potential, the next phase of stress changes is resistance, which includes hypocoagulаemia and increased fibrinolytic activity. This protective response is provided by the mobilization of oxytocin and kinin–kallikrein system as well as anticoagulation and fibrinolytic factors. Intensified fibrinolysis is accompanied by an increase in plasmin activity, greater action of plasminogen activators, and antiplasmin inhibition. In conditions associated with increased fibrin formation, a reactive rise in plasmin levels is observed; at the same time, the concentration of the plasmin–antiplasmin complex increases. When the load exceeds the body’s adaptive capabilities, a state of hypercoagulation develops, accompanied by the inhibition of the anticoagulant system and fibrinolytic activity. The purpose of this article was to analyse the relationship between hormonal status and fibrinolytic activity under physical load during the training process in athletes in order to identify general patterns of the body’s adaptation to physical activity. Materials and methods. The study involved 98 athletes aged between 16 and 25 years doing various sports and living in a subarctic region of Russia (Arkhangelsk Region). Their median age was 19.5 years. Physical activity was considered as a stressor; the state of the haemostatic and endocrine systems was studied. Using the enzyme immunoassay method, the concentrations of thyroidstimulating hormone, free thyroxine, cortisol, testosterone, and plasmin–antiplasmin complex in the venous blood were determined. Results. The study revealed activation of the hypothalamic-pituitary-adrenal axis in athletes, manifested in an increase in cortisol serum levels. This increase confirms the assumption of the predominance of catabolic reactions in athletes. A direct relationship between the concentrations of cortisol and plasmin-antiplasmin complex (Spearman correlation: rS = 0.229; p ≤ 0.05) was established, demonstrating the uniformity of these markers during adaptation to physical load.